2017
DOI: 10.1111/jcpp.12735
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: The effects of atypical antipsychotics and mood stabilisers in the treatment of depressive symptoms in paediatric bipolar disorder

Abstract: These results mostly overlap with the approved treatments for bipolar depression in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 108 publications
(177 reference statements)
1
8
0
Order By: Relevance
“…3B), which was distinct from the outcome of higher doses. Although the reason is unknown, it might be consistent with clinical reports that olanzapine could have antidepressant effects during the treatment of bipolar depression (31). We then tested the efficacy of the high-dose olanzapine treatment (1.0 mg/kg) on the behavioral abnormalities of the Syt7 KO mice using the LH/SPT/LDB paradigms.…”
Section: Identification Of Syt7 As a Candidate Risk Factor For Neuropsupporting
confidence: 56%
“…3B), which was distinct from the outcome of higher doses. Although the reason is unknown, it might be consistent with clinical reports that olanzapine could have antidepressant effects during the treatment of bipolar depression (31). We then tested the efficacy of the high-dose olanzapine treatment (1.0 mg/kg) on the behavioral abnormalities of the Syt7 KO mice using the LH/SPT/LDB paradigms.…”
Section: Identification Of Syt7 As a Candidate Risk Factor For Neuropsupporting
confidence: 56%
“…As polypharmacy is a common clinical practice, investigation of whether psychiatric drugs with anti-inflammatory properties may attenuate metabolic side effects of pro-inflammatory drugs when administered simultaneously [18]. This is the Lithium (Li) case, that is an efficient mood modulator molecule concomitantly used in management of acute mania or manic episodes associated with bipolar disorder [19] and to treat some mixed episodes of major depressive and bipolar disorders [20]. Moreover, the combination of Li plus OLZ has been indicated to treat some mixed episodes of major depressive and bipolar disorders [2,20].…”
Section: Introductionmentioning
confidence: 99%
“…This is the Lithium (Li) case, that is an efficient mood modulator molecule concomitantly used in management of acute mania or manic episodes associated with bipolar disorder [19] and to treat some mixed episodes of major depressive and bipolar disorders [20]. Moreover, the combination of Li plus OLZ has been indicated to treat some mixed episodes of major depressive and bipolar disorders [2,20]. Previous in vitro study also suggested that Li could modulate in vitro proinflammatory macrophage response exposed to some antidepressant drugs [21].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis using repeated-measures mixed models showed that those on AT monotherapy (the reference group) had a gradually diminished, but statistically significant, monthly increase in BMI during all durations of drug exposure (3 When compared to AT monotherapy, the magnitude of increase in BMI associated with MS, AD monotherapy, and no treatment was significantly less at all time points; data indicated less steep slopes of BMI change over time compared with AT monotherapy, especially during the short-term exposure. The combinations of AT with other psychotropic medications (AT+MS, AT+AD) were associated with a similar BMI increase as AT monotherapy.…”
Section: Psychopharmacotherapy In Children and Adolescentsmentioning
confidence: 99%
“…When the risks of ADT use in this age group is matched with the benefits, it appears best that ADT use be limited to moderate-to-severe depression, where psychosocial interventions are either ineffective or not feasible. Practitioner review: The effects of atypical antipsychotics and mood stabilisers in the treatment of depressive symptoms in paediatric bipolar disorder (3) The management of depressive and mixed symptoms in children and adolescents with bipolar disorder (BD) remains a matter of debate. This review systematically examines the impact of atypical antipsychotics (AAPs) and mood stabilisers in the treatment of bipolar depression and/or mixed states.…”
Section: Ariyasinghe Ss Williamsmentioning
confidence: 99%